TRAINING TECHNIQUES FOR CULTIVATION OF THE SAME PLANTS (ANTHOCEPHALUS MACROPHYLLA) IN URSANA HAMLET, HONITETU VILLAGE, INAMOSOL DISTRICT, SERAM REGENCY, WEST MALUKU - Markus Matinahoru, Johan (LPPM Univ. Ibn Khaldun Bogor, 2022)
Wood originating from Indonesian forests is recognized for its high quality, both as building materials and as industrial raw materials. To get quality wood, it takes a long time to replace trees that are cut down for at least 15-20 years. The rate of reduction of trees in forests is not balanced with their growth, so that forest areas in Indonesia are shrinking rapidly from year to year. To compensate for the increasing demand for wood, wood plants are needed that are able to produce wood quickly. Jabon Merah or Samama (Anthocephalus macrophyllus) is a fast growing local plant species with a wide spectrum of uses. In several places in Indonesia this species has begun to be developed and planted by the community. The Samama plant has been cultivated as a trading commodity on a wide scale, starting from the procurement of seeds, nurseries, plantations, wood and their processed products. Samama plants, apart from being used for the development of Industrial Plantation Forests (HTI), can also be used for reforestation and reforestation programs as well as other social forestry. Samama's growth productivity is very high, namely: the increase in the volume of wood above 20-25 m3 / ha / year for 6-8 years. The annual increase in the height of the samama tree reaches 1.5 meters, with an increase in trunk diameter of 5 cm/year. This means that in 15 years with fertile soil conditions and good cultivation techniques, a samama tree with a height of 25-30 m and a diameter of 75 cm can be produced. The development of samama plants as community forests or customary forests will have economic prospects and market certainty in the future. Therefore, it is hoped that this training can encourage farmers to plant and develop samama crops to help their economy. If the samama plant is cultivated properly, in 1 ha of samama plantation for 15 years, it can generate an income of 3 billion rupiah because the current market price for 1m3 of processed wood in the Ambon market is 3 million rupiah.